If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -1) = 4(3 + 3y) Reorder the terms: 3(-1 + y) = 4(3 + 3y) (-1 * 3 + y * 3) = 4(3 + 3y) (-3 + 3y) = 4(3 + 3y) -3 + 3y = (3 * 4 + 3y * 4) -3 + 3y = (12 + 12y) Solving -3 + 3y = 12 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. -3 + 3y + -12y = 12 + 12y + -12y Combine like terms: 3y + -12y = -9y -3 + -9y = 12 + 12y + -12y Combine like terms: 12y + -12y = 0 -3 + -9y = 12 + 0 -3 + -9y = 12 Add '3' to each side of the equation. -3 + 3 + -9y = 12 + 3 Combine like terms: -3 + 3 = 0 0 + -9y = 12 + 3 -9y = 12 + 3 Combine like terms: 12 + 3 = 15 -9y = 15 Divide each side by '-9'. y = -1.666666667 Simplifying y = -1.666666667
| X^2-4y=-28 | | (3y-27)(y^2+8y+15)=0 | | 0.60(z-300)+0.05=0.70z-205 | | x+(x*0.07)=250000 | | y=4x-9-x^3 | | 2+x+20=44 | | 0.50x+20=3x | | -4.9t^2-20t+5=0 | | 7x-6x-7=10 | | -16x^2+32x+7=0 | | Y^4+9y^2+20=0 | | -6x+9x=6 | | -4x+3x=-10 | | X^2-7x-800=0 | | 7-4x=6x-23 | | -7x+3x+9=-3 | | -35=-3x+5+5x | | -7+3x+9=-3 | | m^4+m^2n^2+n^4=0 | | 7(8/5) | | a^2-b^2-10a+25= | | 8/5(7) | | 4x-3x-10=-2 | | (x^3)+6(x^2)+11x+6=0 | | x+2+x+x=6-3 | | F(x)=4x-9-x^3 | | 7k+6=69 | | 4-7(3x-1)=-4x+28 | | 127=(16*59.3/x)(16*9.9/x) | | p-8=-15/p | | -6x+7+7x=9 | | x-sqrt(11-10x)=-22 |